THE INFLUENCE OF SELF BRAND CONNECTION ON LOYALTY: BRAND EXPERIENCE AS A MEDIATOR - Tjandra Rahardja, Conny; Karmila (LPPM STIE YKPN Yogyakarta, 2024)
This study involved 145 respondents from the second wave pioneer coffee product, with an interest in seeking answers: does the second wave coffee product still have loyalists, even though it has been overshadowed by the massive and widespread third and fourth wave coffees in every area? The study employed two independent variables, namely Self Brand Connection (SC) and the mediating variable Brand Experience (BE). The researchers were interested in analyzing the direct and indirect effects of the independent variables on consumer loyalty through a case study on the second wave coffee pioneer company. In this study, the indirect effects were mediated by BE. Primary data were obtained by distributing questionnaires using the Likert scale. The research data were processed using SPSS22 to present descriptive statistical results, validity and reliability tests, classical assumption tests, regression tests, and Sobel tests to test mediation. The results showed that SC has a positive direct and indirect effect on loyalty. In this study, the indirect effect is categorized as partial mediation.